A Study of Interactions between Lead Time Variability and Material Requirements Planning (MRP) performance VIA Simulation - Ting, Leslie Sze Hin (2012)
The purpose of this study is to investigate the effect of lead time variability on Material Requirements Planning (MRP) performance. This study attempts to understand the impact of lead time variability in order to provide insight in dealing with lead time uncertainty in MRP system. Thus, this study aims to investigate the effect of lead time variability at different production level and examine the effectiveness of safety lead time in dealing with lead time uncertainty. In this study, a series of experiments are conducted. The experiments begin with single lead time variability at different production level (i.e. bottleneck process/common required component, lowest BOM level, first BOM level and end item) with varying levels of lead time variability (i.e. low lead time variability and high lead time variability or moderate lead time variability). Then the experiments are extended to multiple lead time variability at the same production level (i.e. lowest BOM level and first BOM level). Safety lead time of one day (Safety Lead Time = 1 and Safety Lead Time = -1) is applied at bottleneck process/common required component in attempt to improve MRP performance. The findings show that common lead time has the greatest impact on MRP performance and therefore it is the first thing manufacturers should deal with. Safety lead time does not improve MRP performance in this case even if optimal safety lead time is applied.